Ethnicity and gender related differences in extended intraesophageal pH monitoring parameters in infants: a retrospective study - Tolia Vasundhara; Thomas Ronald; Nazer Dena (BMC, 2005)
Abstract Background Gastroesophageal reflux disease (GERD) is believed to be more common in adult males as compared to females. It also has been shown in adults to be more common in Caucasians. We wanted to determine ethnicity and gender related differences for extended pH monitoring parameters in infancy. Methods Extended pH monitoring data (EPM) from infants <1 year of age were reviewed. Results were classified in two groups, as control and Gastroesophageal reflux disease (GERD) group based on the reflux index (RI). The GERD group had RI of equal to or more than 5% of total monitoring period. The parameters of RI, total number of episodes of pH < 4, and the number of episodes with pH < 4 lasting more than 5 minutes were compared by genders and by ethnic groups, Caucasians and African American (AA). Results There were 569 infants, 388 controls, 181 with GERD (320 males, 249 females; 165 Caucasians, 375 AA). No statistical difference in EPM parameters was detected between genders in both groups. However, Caucasian infants had a significantly higher incidence of GERD than AA infants (p = 0.036). On stratifying by gender, Caucasian females had a significantly higher number of reflux episodes >5 minutes as compared to AA females in the control group (p = 0.05). Furthermore, Caucasian females with GERD showed an overall higher trend for all parameters. Caucasian males had a trend for higher mean number of reflux episodes as compared to AA males in the control group (p = 0.09). Conclusion Although gender specific control data do not appear warranted in infants undergoing EPM, ethnic differences related to an overall increased incidence of pathologic GERD in Caucasian infants should be noted.